Product Portfolio Restructuring: Methodology and Application at Caterpillar. Issue 1 (9th October 2017) - Shunko, Masha; Yunes, Tallys; Fenu, Giulio; Scheller‐Wolf, Alan; Tardif, Valerie; Tayur, Sridhar
Abstract : We develop a three‐step methodology to restructure a product line by quantifying the restructuring's likely effects on revenues and costs: (i) Constructing migration lists to capture customer preferences and willingness to substitute; (ii) Explicitly capturing the (positive and negative) cost of complexity across different functional areas, using statistical analysis of cost data; and (iii) Integrating these tools within a mathematical optimization program to produce a final product line, incorporating the possibility of differentiating products by lead‐time (into different lanes ). Our methodology is highly flexible—each step can be tailored to a company's particular setting, data availability and strategic needs, so long as it produces the necessary output for the next step. We report on the successful application of our methodology to the Backhoe Loader product line at Caterpillar: In collaboration with Caterpillar, we were able to significantly simplify this line, reducing the number of configurations from 37, 920 to 135, in three lanes, while increasing sales by almost 7%.